LO58: An education needs assessment: how can we optimize the education provided to off-service residents completing an emergency medicine rotation. (May 2019) - Stiell, A.; Karram, J.; Cheung, W.; Frank, J.
Abstract : Introduction : Over 150 Off Service Residents from 18 different programs rotate through our ED every academic year. We aim to determine the educational needs of these residents to we better design a curriculum for their ED rotation.Methods : We conducted a cross-sectional convenience sample survey of 133 Off-Service PGY-2 residents who had rotated through the ED of The Ottawa Hospital in their PGY-1 year. (from July 2016 to June 2017). The survey was emailed to residents from March to May 2018 and consisted of 19 questions. Questions were qualitative, selection from list and rank order. They focused on 3 main areas: EM rotation impact and areas for improvement, desired content, desired method of learning. Data was collected using Survey Monkey.Results : We received 70 responses (53%) from 13 different residency programs. 36 (51.4%) of respondents were from the Family Medicine program. Qualitative themes included that the ED provides great opportunity to develop the ability to workup undifferentiated patients and allows for teaching around cases. Allowing more involvement in acute care cases and having more SIM sessions could improve the rotation. The most useful topic was chest pain/cardiovascular conditions (73.3% of residents) with 16 additional ED topics listed as important for their practice. The most useful skill was suturing (51.6% of residents) with 16 other ED procedures listed as important for their practice. The preferred teaching method was SIM (48.3%) followed by small group teaching (33.3%).Conclusion : The emergency department provides an excellent learning environment for a large range of Off-Service residents early in their training. In addition to clinical shifts, a curriculum incorporating simulation and small group teaching and that covers a large scope of topics is necessary to meet the needs of these residents.